Unlocking Indonesia’s Critical Minerals for Renewable Energy: Challenges and Pathways to Net-Zero Emissions - Andrew Cahyo Adhi; Nur Widi Priambodo; Muchammad; Suryo Utomo, Tony; Akmal Setia Abdrian, Reyhan Kevin (Science and Technology Research Centre Universitas PGRI Semarang, 2025)
Indonesia holds a pivotal role in the global renewable energy (RE) transition due to its abundant reserves of critical minerals like nickel, cobalt, and rare earth elements (REEs). However, a significant gap exists between these resources and the technologies needed to leverage them, highlighting supply chain vulnerabilities. This qualitative, exploratory-descriptive study integrates Life Cycle Assessment (LCA), criticality matrix analysis, and value chain mapping to examine Indonesia’s mineral supply chains, sustainability, and Local Content (TKDN) policies. The findings reveal that despite its mineral wealth, Indonesia's inadequate management capacity complicates the achievement of TKDN goals and exposes supply chain deficiencies. The research advocates for developing downstream industries, adopting sustainable mining practices, and international collaboration. Policy recommendations include simplifying regulations, fostering innovation, and embracing circular economy principles, providing Indonesia with a strategic framework for its energy transformation.